2020
DOI: 10.1093/hmg/ddaa035
|View full text |Cite
|
Sign up to set email alerts
|

Knockin mouse model of the human CFL2 p.A35T mutation results in a unique splicing defect and severe myopathy phenotype

Abstract: Cofilin-2 is an actin-binding protein that is predominantly expressed in skeletal and cardiac muscles and belongs to the AC group of proteins, which includes cofilin-1 and destrin. In humans, cofilin-2 (CFL2) mutations have been associated with congenital myopathies that include nemaline and myofibrillar myopathy. To understand the pathogenicity of the human CFL2 mutation, p.A35T, that first linked cofilin-2 with the human disease, we created a knock-in mouse model. The Cfl2A35T/A35T (KI) mice were indistingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A novel KI-mouse model harbouring the first human missense mutation linking the gene to NM mimicked the phenotype of the KO mice. The KI model was normal at birth, but rapidly deteriorated and died by postnatal day nine [83] .…”
Section: Regulatory Proteinsmentioning
confidence: 99%
“…A novel KI-mouse model harbouring the first human missense mutation linking the gene to NM mimicked the phenotype of the KO mice. The KI model was normal at birth, but rapidly deteriorated and died by postnatal day nine [83] .…”
Section: Regulatory Proteinsmentioning
confidence: 99%
“…We chose to study the function of the CFL2 gene in embryonic skeletal muscle development further. The role of CFL2 has been studied in cardiac muscle (Vafiadaki et al, 2020) and many types of congenital myopathies (Rosen et al, 2020), but not in chicken skeletal muscle development. Qian et al (2017) found significant differences in the CFL2 gene in chicken leg muscle transcriptomes of different ages.…”
Section: Discussionmentioning
confidence: 99%
“…The HEK293, 293A and C2C12 cell lines were the preservative cell lines from American ATCC in our laboratory. Primary bovine myoblasts (PBMs) were harvested from fetal bovine longissimus dorsi muscle and cultured by collagenase-I digestion as previously described [ 13 ]. Cell lines and PBMs were cultured following our previously established protocols [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Considering CFL2 a candidate gene for nemaline myopathy, some studies have shown that the mutation from G to A in the coding region position 103 of the CFL2 gene can induce the occurrence of human nemaline myopathy, and the CFL2 gene can regulate the expression of key factors CAM and MEF2C in myofibroblast signal pathway, resulting in a change in muscle properties [ 12 ]. A CFL2 A35T/A35T knock-in mouse model indicated that the expression levels of CFL2 mRNA and full-length transcript decreased significantly in skeletal muscles and muscle biopsy samples of a p.A35T mutation patient, respectively [ 13 ]. Sun examined the association of the CFL2 gene polymorphisms with performance traits in Qinchuan (QC) cattle.…”
Section: Introductionmentioning
confidence: 99%